Failure of Posterior Capsulolabral Repair is Correlated with Percent of Glenoid Bone Loss. Issue 7 (30th July 2021) - Provencher, Matthew; Ruzbarsky, Joseph; Peebles, Liam; Midtgaard, Kaare; Bradley, James; Arner, Justin
Objectives: The purpose of this study was to evaluate previously described advanced MRI measures specific to posterior bone loss on both standard and manually reformatted MRIs in patients who underwent posterior shoulder capsulolabral repair. It was hypothesized that those who failed surgical repair would have increased posterior glenoid bone loss and decreased glenoid width. Methods: Athletes greater than 18 years of age with unidirectional posterior instability treated with arthroscopic repair were evaluated at 2 year minimum follow-up. Traditional MRIs measurements from nineteen patients who failed arthroscopic posterior shoulder capsulolabral repair were compared with 56 patients who did not. MRIs were then manually reformatted and these measurements were repeated as well as recently described measures of defect slope, bone loss angle, and defect length. Results: Glenoid width loss and percent glenoid bone loss were significantly greater on both the corrected and non-corrected MRI images (25.5 mm vs 28.8 mm, p<0.001; 6.8% vs 4.6%, p=0.008) in those that failed surgery. There was no difference in glenoid version or other measurements between the failures and non-failures. On non-corrected MRIs, percentage glenoid bone loss was significantly overestimated by 2% when compared to the corrected scans (p<0.0001, 95% CI [-2.7, -1.1]). A critical amount of 11% glenoid bone loss resulted in a 10 times higher surgical failure rate while 15% bone loss resulted in a 25 times higher failure rate. Conclusions: Risk factors for failure of arthroscopic posterior shoulder capsulolabral repair include greater glenoid bone width loss and greater glenoid bone loss percentage. Failure to appropriately align axial MRI rotation affects the characteristics of the sagittal images, leading to overestimation of glenoid bone loss percentage which may have surgical implications. Although 11% glenoid bone loss implicated a 10 times higher surgical failure rate and 15% bone loss has a 25 times higher failure rate, posterior capsulolabral repair is an overall successful intervention.